2014
DOI: 10.1016/j.pedneo.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Neonates' Macrosomia with Maternal Lipid Profile of Healthy Mothers

Abstract: Maternal triglyceride levels may be a significant predictor of fetal size in late pregnancy but not in early pregnancy. Our study reinforces that this is true not only in the case of macrosomia (birth weight > 4500 g), but also for LGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 16 publications
3
33
0
5
Order By: Relevance
“…Some researchers have reported that only in obese pregnant women is the HDL-C value in late pregnancy negatively correlated with NBW [25]. Mossayebi et al reported that TG is a predictor of NBW in nondiabetic and nonobese pregnant women [26]. It has also been reported that the TC and LDL-C values in pregnant women are related to neonatal weight [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have reported that only in obese pregnant women is the HDL-C value in late pregnancy negatively correlated with NBW [25]. Mossayebi et al reported that TG is a predictor of NBW in nondiabetic and nonobese pregnant women [26]. It has also been reported that the TC and LDL-C values in pregnant women are related to neonatal weight [27].…”
Section: Discussionmentioning
confidence: 99%
“…TG cannot be transported through the placenta, but it can be hydrolyzed to free fatty acids (FFA) by lipoprotein esterase in the placenta. A high level of FFA can result to high levels of fat and glucose being deposited in the fetus due to the passage of FFA through the placenta; this may ultimately lead to LGA infants [26]. The cholesterol of mothers can be transported to the fetus through the placenta and further regulate the synthesis of fetal cholesterol, thereby affecting the size and weight of the fetus [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although an independent association between glucose and LDL-cholesterol with LGA was shown in our study, the contribution to the predictive performance was minimal (Table 3). The lack of association with triglycerides may reflect the time of measurement at 14–16 weeks, which may have little relevance to later fetal growth, [25] or, alternatively, previously observed association could be explained by unmeasured confounders, as this association was also not apparent using mendelian randomisation [21]. VEGFR1 is the receptor for vascular endothelial growth factor (VEGF) and provided a mild increase in the AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Different components of the metabolic syndrome are also risk factors for LGA (i.e. obesity, impaired glucose metabolism and hypertriglyceridemia), which therefore could explain the higher prevalence of metabolic syndrome in women with LO‐PE without a SGA infant than in those with LO‐PE and SGA in our study.…”
Section: Discussionmentioning
confidence: 71%